The determinants of directors’ remuneration in the Malaysian public listed companies / Fattiadriati Mohd Tareh - Mohd Tareh, Fattiadriati (2019)
One of the main controversial issues arises from the weaknesses in the corporate governance practices is the directors’ remuneration. The question raised is whether the remuneration paid to the directors is consistent with the interest of the shareholders. Therefore, the main aim of this study is to identify the key determinants of directors’ remuneration in Malaysia. This study examines the relationships between the company’s characteristics and corporate governance characteristics with directors’ remuneration. For this research, the company’s characteristics selected are the company size, company leverage, company performance. Meanwhile, the corporate governance characteristics selected are the board leadership structure and the independence of the remuneration committee. A sample of 260 public listed companies on Bursa Malaysia was selected using stratified random sampling for the financial reporting year 2018. All data concerning company and corporate governance characteristics are obtained from the annual reports of the company which are accessible from the Bursa Malaysia website. Pearson correlation and multi regression was used to analyses the data to determine the relationship of the predictor variables with directors’ remuneration. It was found that only company size showed a significant positive relationship with directors’ remuneration. Company performance showed a positive but weak relationship with directors’ remuneration, which suggest that the remuneration paid to directors are not linked to company performance. The remaining predictors have no relationship with directors' remuneration. The findings suggest that the larger the company, the higher would be the remuneration paid to the directors. Besides, the directors' remuneration is not depending on the profit made by the company. Lastly, company compliance with the recommendation of Malaysian Code on Corporate Governance does not guarantee the effectiveness of the monitoring function of the remuneration committee in ensuring that the directors' remuneration is commensurate with the company performance.